The Effective of Marriage Betery on The Life of Family: An Analytical Research (Raparin Journal of Humanities (RJH), 2024)
The current study aims to know the main causes of marital in fidelity &its impact on families and children in particular & on society in general .The study merstigates the preralence  of marital infidelity its types it also attempts to discover the motivating  factors that leads to conduct this act in addition, the impact  of such action in addition, the impact of such action on families as well as various of betrayal methods to prevent the spread of betrayal is also identified by the researcherThe type of the study is qualitative& description approach is used by the research to study the case & the interview with  observation tools are used to collect data  with narrative tools to singinfy on the case research. The researcher took 5cases in Erbil city center .samples are from several  governmental institutions thar are specialized in reform, adoption also protecting individuals from Any from of violence or Threat. For instance, Erbil Shelter Directorate, women &Children reform  Directorate ,Detention &transfer Directorate)The study concludes thar one of the  main reason for infedility in most of the cases is the feeling of revenge that one of the spouses hold against the other due to the absence of the partner that creates an emotional & sexual gap & leads to neglect.In addition, imitating dubbed dramas had an impact on prevalence of this phenomenon.